PENGARUH PENGEMBANGAN MANAJEMEN KINERJA KLINIS (PMKK) TERHADAP KINERJA PERAWAT DI IGD RS. DR. M. DJAMIL PADANG - Devi Verini (Jurnal Kesehatan Medika Saintika, 2010)
Dr. M. Djamil Hospital in Padang as health provider, teaching and qualified research hospital, and referral hospital in Central Sumatera aims to increase people health degree by increasing profession nurses performance. Emergency department service has complex services and knowledge multidiscipline that influences other health services. The fact, nurses in this hospital are doing non nursing job that caused conflict with patients, nurses, and other medical staffs. Developing system of clinical performance management is one strategy for increasing nursing service quality and nursing performance that implemented as in policy of health ministry no. 836/2005 to be policy of quality and well nursing performance in hospital and primary health services (Tjahjono Kuntjoro, 2005). The study aimed to find out the influence of developing system of clinical performance management toward nurses performance with 5 major component of assessment, that were standard, job description, performance indicator, cases reflection, discussion monitoring and evaluation. This was experiment quasy study with one group pre and post test. Sample was obtained using quota sampling method toward 22 nurses in trease emergency departement and 8 staffs in pre operative room. The study was obtained for one month, started from second week in April until second week of May and three weeks of evaluation. The result of the study showed significant influence of developing system of clinical performance management training toward nurses performance skills with P = 0,000 (P < 0,05), nurses attitude toward their performance with P = 0,000 (P < 0,05), and insignificantly influenced nurses personal performance with P = 0,121 (P > 0,05), nurses knowledge toward nursing care of emergency departement with P = 0,121 (P > 0,05), nursing care standard documentation from 24 substance, 16 of them generally has significant influenced with P = 0,000 (P > 0,05) and 8 of them has no influenced before and after developing system of clinical performance management training. Training of developing system of clinical performance management is effective enough in increasing nurses performance but monitoring and evaluation should keep be obtained continuously.